THE THE FOUR SQUARE STEP INTERVENTION IS MORE EFFECTIVE IN IMPROVING THE DYNAMIC BALANCE RATHER THAN BALANCE STRATEGY EXERCISE IN THE ELDERLY OF VILLAGE OF TONJA, EASTERN DENPASAR, BALI - Laksmita, Putu Ayunia; Andayani, Ni Luh Nopi; Artini, I Gusti Ayu (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
Dynamic balance is the ability to maintain body position while moving. The purpose of this study was to determine the effect of four square step interventions that is more effective in improving the dynamic balance rather than balance strategy exercise. This research is an experimental design using Pre and Post Test of Two Group Design. The results showed an increase in dynamic balance in the treatment of group 1 of 3.222 and there was an increase of 4,444 in the treatment group 2. Results of paired samples t-test found a significant difference with p = 0.000 (p <0.05) in the treatment group 1 and p = 0.000 (p <0.05) in the treatment of group 2. The differential test of Mann Whitney u test showed no significant difference between the treatment group 1 and treatment group 2 in which p = 0.01 (p <0.05). It can be concluded that the four square step interventions is more effective in improving the dynamic balance rather than the balance strategy exercise in the elderly. Keywords: dynamic balance, balance exercise strategy, four square step